The partnership between the public and private sectors as an alternative option to treat the deficit in the state s' general budget (Damascus University Journal for legal sciences, 2024)
It increased  with the emergence of the financial  deficit in many countries. The search for many ways   to confront the fiscal deficit in the public budget. The method of participation between the public and private sectors is on of the alternative mothed to confront of the financial  deficit, especially after the failure of the measures taken by countries, including  (Increasing domestic revenues - Improving tax collection procedures - Combating tax evasion - Accelerating the completion of tax accumulation - Increasing investment revenues - Control and rationalization of public spending) Because such measures taken by countries in order to reduce the deficit, especially on the revenue side seem largely outside the control of the financial authorities Whether due to political conditions or global economic conditions, and currently the Corona pandemic. The state’s resort to concluding such contracts is a new methodology in order to reduce the financial burdens borne by its budget, as the participatory method allows the establishment of economic projects without the use of public resources. Funding from the private sector generally allows the transfer of financial, industrial and other risks to the project company.
Keywords: Participation; Privatization; Public Sector; Private Sector.